2019
DOI: 10.5114/aoms.2019.87095
|View full text |Cite
|
Sign up to set email alerts
|

Expression of miRNAs-122, -192 and -499 in end stage renal disease associated with acute myocardial infarction

Abstract: IntroductionNew diagnostic tools are needed to accurately detect acute myocardial infarction (AMI) in patients with end stage renal disease (ESRD) presenting with ischemic chest pain. We aimed in this study to investigate circulating miR-122, -192 and -499 expression levels in patients with AMI on top of ESRD and evaluate the potential of these miRNAs as blood-based biomarkers for AMI in patients with ESRD.Material and methodsThe study included 80 ESRD patients without AMI, 80 patients with ESRD associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Mir-192 is one of the earliest miRNAs that could regulate DNinduced pathological pathways. It was highly expressed in renal tissue and played a key role in renal development and differentiation (Abdelsalam et al, 2019). Later experiments showed that mir-192 could promote the fibrosis of glomeruli and tubules (Mu et al, 2013).…”
Section: Micrornasmentioning
confidence: 99%
“…Mir-192 is one of the earliest miRNAs that could regulate DNinduced pathological pathways. It was highly expressed in renal tissue and played a key role in renal development and differentiation (Abdelsalam et al, 2019). Later experiments showed that mir-192 could promote the fibrosis of glomeruli and tubules (Mu et al, 2013).…”
Section: Micrornasmentioning
confidence: 99%
“…f) gut microbiota and chronic kidney disease: CVD and kidney diseases are closely interrelated (e.g., cardiorenal syndrome). Patients with chronic kidney disease (CKD) have a greater risk of CVD complications as well as an increased mortality rate, therefore, in many research environments, they are trying to identify the most appropriate biomarkers of potential complications (29). Studies have confirmed that patients with CKD have a distinctly different composition of gut microbiota.…”
Section: IImentioning
confidence: 99%